The relationship of self-awareness with the power of cognitive control among students of the University of Sharjah - Al-Akashee, Bushra Ahmed (Al-Adab Journal, 2019)
The aim of the study was to reveal the level of self-awareness and the cognitive control power of university students for the academic year 2017-2018 and to reveal the relationship and differences between them according to the gender variable. To achieve this goal, the researcher prepared two study tools: self-awareness measurement tool and cognitive strength control tool, which were verified and validated and were applied to a random sample of 300 students from the University of Sharjah. The results of the study showed that the members of the current research sample have a high level of self-awareness, and they have an average level in the cognitive control strength variable and there is a significant difference in the self-awareness scale of the subjects (emotional awareness, accurate self-evaluation) in favor of female students, In the measure of the power of cognitive control in the sex variable. And a statistically significant relationship between self-awareness and cognitive control power in the study sample.